Efficient heuristics for cost optimisation in multi stage supply chain network with a fixed transportation charge. (1st January 2014) - Manimaran, P.; Selladurai, V.
This paper addresses multi stage supply chain network (MSCN) problem associated with fixed cost. The MSCN problem involves the selection of suppliers, locating manufacturing plants and distribution centres and determining the optimum/best strategy for distributing the products from the plants to the distribution centres and from the distribution centres to the customers. The objective is to select the optimum numbers, locations and capacities of plants and distribution centres to open so that all customer demand is satisfied at minimum cost. The problem chosen goes beyond the traditional mathematical programming and it becomes a non-polynomial (NP) hard while considering the fixed costs. We develop a mixed integer programming model and provide an efficient heuristic solution procedure for this distribution system problem. Several numerical experimental results are presented and compared with the approximate and lower bound solutions to show the effectiveness of the proposed method. The comparison reveals that the proposed heuristics generates better solution than the approximation method and closer to lower bound solutions.